PKM Meningkatkan Kesadaran dan Perlindungan Pengguna di Era Digital Bagi Para Remaja di Desa Larangan Luar Pamekasan - Abdul Bari; Achmad Taufik; Ria Kasanova (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The use of digital technology has permeated various aspects of daily life, even in remote villages such as Desa Larangan Luar Pamekasan. In addition to providing significant benefits, these technological advances also bring new challenges related to privacy and data security. This research aims to raise awareness of digital law and privacy protection in Larangan Luar Village through a structured educational approach. Involving village youth as the main target group, the community service programme included digital law education sessions, workshops on digital privacy and security, and interactive discussion forums. Pre- and post-programme surveys showed a significant increase in participants' understanding of digital law, with an average increase of around 35%. In addition, the evaluation also revealed that approximately 85% of participants had adopted new digital security practices after participating in the programme.